Pentacam-based big bubble deep anterior lamellar keratoplasty in patients with keratoconus - Riss, Stephan; Heindl, Ludwig M.; Bachmann, Bjoern O.; Kruse, Friedrich; Cursiefen, Claus (Cornea, 2012)
To describe the clinical results of Pentacam-based big bubble deep anterior lamellar keratoplasty (DALK) to achieve an intended 90% depth of initial lamellar trephination.Fifty consecutive eyes of 50 patients with keratoconus, keratoglobus, and anterior stromal scars were included. DALK was performed with the big bubble technique using a 90% intended depth for initial lamellar trephination based on preoperative pachymetry by Pentacam. Main outcome measures were success of surgery, best spectacle-corrected visual acuity, endothelial cell count, refractive astigmatism at 12-month follow-up, and rate of intra- and postoperative complications.In 84% of the patients (n = 42), Pentacam-based big bubble DALK could be performed successfully. Successful big bubble formation could be achieved in 80% of the patients (n = 34). In case of macroperforation (n = 8), surgery was converted to standard penetrating keratoplasty representing a conversion rate of 16%. Intraoperative microperforation (n = 5) could be handled by an intracameral air injection at the end of operation with successful completion of the lamellar procedure. No allograft rejection was observed. Best spectacle-corrected visual acuity improved from 20/125 ± 20/160 preoperatively to 20/40 ± 20/80 at 12-month follow-up. Endothelial cell count was 2102 ± 318 cells per square millimeter preoperatively and 1735 ± 420 cells per square millimeter at 12-month follow-up. Refractive astigmatism was 7.09 ± 3.13 diopters preoperatively and decreased to 4.13 ± 2.41 diopters.Pentacam-based big bubble DALK using a 90% intended depth of initial lamellar trephination seems to be a safe and effective procedure for anterior corneal stromal disorders such as keratoconus. We suggest that Pentacam-based depth assessment allows for reliably deep initial preparation and may allow more successful bubble formation in DALK surgery.
EVALuna2:21074